Bisphosphonates-much more than only drugs for bone diseases - Kuźnik, Anna; Październiok-Holewa, Agnieszka; Jewula, Pawel; Kuźnik, Nikodem (European journal of pharmacology, 2020)
α,α-Bisphosphonates (BPs) are well established in the treatment of bone diseases such as osteoporosis and Paget's disease. Their successful application originates from their high affinity to hydroxyapatite. While the initially appreciated features of BPs are already beneficial to many patients, recent developments have further expanded their pleiotropic applications. This review describes the background of the interactions of BPs with bone cells that form the basis of the classical treatment. A better understanding of the mechanism behind their interactions allows for the parallel application of BPs against bone cancer and metastases followed by palliative pain relief. Targeted therapy with bone-seeking BPs coupled with a diagnostic agent in one particle resulted in theranostics which is also described here. For example, in such a system, BP moieties are bound to contrast agents used in magnetic resonance imaging or radionuclides used in positron emission tomography. In addition, another example of the pleiotropic function of BPs which involves targeting the imaging agents to bone tissues accompanied by pain reduction is presented in this work.
Keywords: Bone imaging; Bone Diseases; nemoci kostí; zvířata; Humans; Paget's disease; Bisphosphonate; Osteoporosis; bisfosfonáty; Diphosphonates; Bone disease; Bone metastasis; lidé; Animals